Direitos autorais nas plataformas de streaming: desafios de artistas em relação a regulamentação e fruição econômica na era digital - Santana, Nayara Moura de (2025)
The research aims to analyze the challenges faced by holders of copyright and related rights amid the rise of streaming platforms and their implications for the music industry. Using a historical and normative approach, it examines the concepts of intellectual property, copyright law, and the emergence and evolution of technological tools that have significantly transformed the consumption and monetization of musical works. In this context, the study highlights the shortcomings of the current Brazilian copyright legislation, Law No. 9,610/98, particularly regarding the economic enjoyment of rights by artists, in light of changes since the late 1990s. For this reason, the research advocates for updating the current legal framework to ensure fair economic compensation for creators and to preserve their rights in the digital era